Prof. Volodymyr Kovalchuk - Invited to 4th TECHNIUM International Conference - Recognition of career: Director of the Computer Science Technology College of the Environmental State University (Odessa)Professor of Computer Science Department of the Environmental State University (Odessa)Ak. Korolova Str. 5/2Odessa, Ua-65101Ukraine - Editor-in-chief, Technium (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Prof. Volodymyr Kovalchuk - Invited to 4th TECHNIUM International Conference - Recognition of career